2014
DOI: 10.1111/aji.12247
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Hormonal Changes in the Female Reproductive Tract Immune Environment during the Life Cycle: Implications for HIV/STI Prevention Research

Abstract: CitationVenkatesh KK, Cu-Uvin S. Anatomic and hormonal changes in the female reproductive tract immune environment during the life cycle: implications for HIV/STI prevention research. Am J Reprod Immunol 2014; 71: 495-504

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 63 publications
(56 reference statements)
1
15
0
Order By: Relevance
“…are in line with the suggestion that sex steroids have a regulatory role in adrenomedullin production by human endothelial cells . All our female subjects were postmenopausal, and characteristic plasma oestradiol depletion and plasma luteinising hormones elevation at this stage of the female life cycle are associated with a higher male‐like level of plasma adrenomedullin . In addition, our subjects were overweight: plasma adrenomedullin positively correlates with BMI, especially in females .…”
Section: Discussionsupporting
confidence: 89%
“…are in line with the suggestion that sex steroids have a regulatory role in adrenomedullin production by human endothelial cells . All our female subjects were postmenopausal, and characteristic plasma oestradiol depletion and plasma luteinising hormones elevation at this stage of the female life cycle are associated with a higher male‐like level of plasma adrenomedullin . In addition, our subjects were overweight: plasma adrenomedullin positively correlates with BMI, especially in females .…”
Section: Discussionsupporting
confidence: 89%
“…This is an area that we have only begun to understand and involves multiple complex biological and clinical factors that need to be carefully evaluated. 55 Several reviews on the subject have been recently published where these aspects are further elaborated. [56][57][58][59] Hepatitis Acute viral hepatitis is the most common cause of jaundice in pregnancy.…”
Section: Rubellamentioning
confidence: 99%
“…During pregnancy, many factors may influence the state of the vagina's immunity to pathogens. For example, changes in the morphology of the vaginal mucosa, the regulation of the mucosal environment, and the hormonal level in the female reproductive tract are essential to resist external pathogens (54). Faure et al found that the vagina could produce an anti-inflammatory response (a 5-fold increase of IL-10) and a strong mucosal homeostasis response (a 40-fold increase of IL-22) to fight BV infection by detecting the vaginal tissue samples of pregnant women infected with BV (55).…”
Section: Resistance To Pathogenic Microorganisms During Pregnancy Defmentioning
confidence: 99%